ผลบรรเทาอาการปวดกล้ามเนื้อและความพึงพอใจของตำรับน้ำมันหอมระเหยสูตรผสม (MUSCLE PAIN RELIEF EFFECT AND SATISFACTION OF BLENDED ESSENTIAL OIL PREPARATION) - กุลบุตร, ไมตรี; หงส์รัตนาวรกิจ, ฐาปนีย์ (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2015)
การศึกษานี้มีวัตถุประสงค์เพื่อศึกษาผลบรรเทาอาการปวดกล้ามเนื้อและความพึงพอใจของตำรับน้ำมันหอมระเหยสูตรผสมในนิสิตพลศึกษา ทำการศึกษาแบบกึ่งทดลอง กลุ่มเดียววัดก่อนหลัง มีผู้เข้าร่วมวิจัยจำนวน 35 คน กลุ่มตัวอย่างจะประเมินอาการปวดกล้ามเนื้อก่อนและหลังการใช้ผลิตภัณฑ์ทาบริเวณที่ปวดรวมทั้งประเมินความพึงพอใจต่อการใช้ผลิตภัณฑ์ดังกล่าวด้วย แบบประเมินระดับความปวดใช้มาตรวัดที่เป็นตัวเลข (0-10) และประเมินความพึงพอใจต่อผลิตภัณฑ์โดยใช้แบบสอบถามในแง่ต่างๆ ได้แก่ ลักษณะทางกายภาพ ความรู้สึกเมื่อสูดดมกลิ่นผลิตภัณฑ์ ความพึงพอใจขณะใช้ ความคิดเห็นภายหลังจากการใช้ และความพึงพอใจภาพรวมของผลิตภัณฑ์ สถิติที่ใช้ในการวิเคราะห์ ได้แก่ ความถี่ ร้อยละ ค่าเฉลี่ยเลขคณิต ส่วนเบี่ยงเบนมาตรฐาน การทดสอบค่าที กำหนดระดับความมีนัยสำคัญที่ 0.05 ผลการศึกษาพบว่า กลุ่มตัวอย่างมีอาการปวดกล้ามเนื้อลดลงอย่างมีนัยสำคัญทางสถิติ (p<0.001) หลังการใช้ผลิตภัณฑ์ ความพึงพอใจในภาพรวมของผลิตภัณฑ์อยู่ในระดับมาก (คะแนนเฉลี่ย 3.77 จากคะแนนเต็ม 5) ความพึงพอใจต่อลักษณะทางกายภาพของผลิตภัณฑ์อยู่ในระดับปานกลาง (คะแนนเฉลี่ย 3.40) กลุ่มตัวอย่างส่วนใหญ่รู้สึกผ่อนคลายหลังการใช้ผลิตภัณฑ์คิดเป็นร้อยละ 74.3 ความพึงพอใจขณะใช้ผลิตภัณฑ์อยู่ในระดับมาก (คะแนนเฉลี่ย 3.49) ความคิดเห็นภายหลังจากการใช้ผลิตภัณฑ์พบว่าผลิตภัณฑ์มีความเหนอะหนะในระดับพอดี (ร้อยละ 60.0) แต่มีความมันบนผิวหนังในระดับมันมาก (ร้อยละ 51.4) กลุ่มตัวอย่างร้อยละ 41.2 มีความตั้งใจซื้อผลิตภัณฑ์หากมีจำหน่ายในท้องตลาด รูปแบบที่เหมาะสมที่สุดสำหรับผลิตภัณฑ์นี้คือ น้ำมันนวดคิดเป็นร้อยละ 55.9 สรุปการศึกษานี้แสดงให้เห็นว่า ตำรับน้ำมันหอมระเหยสูตรผสมนี้มีแนวโน้มที่จะใช้เป็นผลิตภัณฑ์ทางเลือกสำหรับบรรเทาอาการปวดกล้ามเนื้อ แต่ควรศึกษาเพิ่มเติมเพื่อยืนยันประสิทธิภาพที่ชัดเจนของผลิตภัณฑ์โดยเปรียบเทียบกับผลิตภัณฑ์ที่มีจำหน่ายในท้องตลาด แม้ว่าความพึงพอใจในภาพรวมของผลิตภัณฑ์อยู่ในระดับมากอย่างไรก็ตามควรปรับปรุงความสามารถในการซึมผ่านและความมันบนผิวหนังของผลิตภัณฑ์เพื่อให้เกิดความพึงพอใจสูงสุด คำสำคัญ: ปวดกล้ามเนื้อ ความพึงพอใจ น้ำมันหอมระเหยสูตรผสม The objective of this study was to investigate the muscle pain relief effect and satisfaction of blended essential oil preparation in physical education students. Study design was a quasi-experimental study with one group pretest post-test. Thirty-five samples participated in this study. The samples assessed muscle pain before and after applying the product as well as rated satisfaction with the use of such product. The severity of pain was assessed by a numerical pain scale (0-10). The satisfaction with the preparation was evaluated by questionnaires in terms of physical appearances, sense of smell on the product, satisfaction with using the product, opinion after using the product, and overall satisfaction of the product. The statistics used to analyze data in terms of frequency, percentage, arithmetic mean, standard deviation, and paired sample t-test. The level of significance set at 0.05. The results showed that samples felt muscle pain decreased significantly after using the product (p <0.001). Overall satisfaction of the product was in high level (average 3.77 of the total 5). Satisfaction with product physical appearances were moderate (average 3.40). After using the product, most samples felt relaxed (74.3%). Satisfaction with using the product was in high level (mean = 3.49). The opinion after using the product showed that the product had a sticky on the skin in moderate level (60.0%), but it had an oily on the skin in high level (51.4%). The 41.2 percentage of samples were willing to buy the product if it was sold in the market. The most suitable formulation for this product was massage oil (55.9%). In conclusion, this study showed that this blended essential oil preparation seems to have potential as an alternative product for muscle pain relief, but there should be more investigate in order to confirm the clear efficacy of this product by compared with products available in the market. Although the overall satisfaction of the product was in a high level, it should improve the ability to penetrate the skin and product’s oily to achieve maximum satisfaction. Keywords: muscle pain, satisfaction, blended essential oil